Umida HOW EFFECTIVE LEARNER TENDS TO BE IN LEARNING LANGUAGE: HOW EFFECTIVE LEARNER TENDS TO BE IN LEARNING LANGUAGE - Hamrayeva, Umida (Журнал иностранных языков и лингвистики, 2022)
In the article the questions about development in learning process standards on foreign language in system of the continous education, in the correspondence of international common world standard of requirements, presented to level of preparing to got knowledge and skills of learners on such types of speech activity as auding. There’s no such thing as being born good at languages. However, there are people who learn languages well. But that has nothing to do with them being naturally good at it. It has to do with their attitude and the way they approach their learning.